Meningkatkan Kemudahan Pembelajaran Digital Marketing Menggunakan Mobile Learning di SMAN 2 Aikmel - Widia Febriana; Rini Anggriani; I Nyoman Yoga Sumadewa; Melati Rosanensi (Universitas Bumigora, 2023)
Technological developments are currently growing rapidly. The rapid development of technology affects the progress of a business marketing process. One of the technological developments in the marketing process is digital marketing. Digital marketing is an attempt to promote a product using internet media with the aim of winning the competition to attract consumers and potential customers efficiently. There are many ways that must be learned to carry out digital marketing so that digital marketing can be carried out efficiently and does not harm a business owner who will carry out digital marketing. Little knowledge of digital marketing in general and little material and android applications that discuss digital marketing that can be accessed online or offline is one of the reasons for the lack of understanding of someone who will develop a learning process at SMAN 2 Aikmel. Researchers made an article with the title